Effects of land use/land cover, bioclimatic, and topographic variables on the seasonal occurrence of eastern equine encephalitis virus in Florida - Joni Downs; Saurav Chakraborty; Sean P. Beeman; Rebecca Loraamm; Kristi Miley; Thomas R. Unnasch (Journal of Land Use Science)
We used the model output to explore relationships between EEEV occurrence and environmental factors, as well as generated risk maps for each season. We also introduced a normalized difference risk index to identify locations with high risk during both seasons. LULC variables were better predictors of EEEV than bioclimatic or topographic variables. Summer cases occurred in locations that were in or near rural lands at high elevations that were near woody wetlands and coniferous forests, while winter cases occurred primarily in areas with large proportions of evergreen forests and rural land. Because EEEV is often fatal to both horses and humans, the goal was to provide more accurate EEEV risk maps for each season to guide disease management and vector control efforts.